Synthetic Cannabinoid Usage Characteristics and Perceptions of Addicts in the Treatment Process - Özcan, Yasemin Sanal (The Bulletin of Legal Medicine, 2022)
Objective: Knowing by whom, in what form a substance is consumed, with which substances it is consumed with, the frequency of use, the effects it creates on the user and the expectations from the use significantly affect the effectiveness of the fight against these substances. It was aimed to reveal the socio-demographical characteristics, adaptation problems, suicidal attempt and self-harm behaviors, synthetic cannabinoid use histories, patterns and effect expectations as well as the perceptions of synthetic cannabinoid (SC) users. Methods: It was conducted through one-to-one interviews with 70 male patients who were receiving substance abuse treatment. Results: 41% (n=29) of the participants were unemployed and 60% (n=42) of them dropped out of school. They encountered problems such as caries (7.1%) and discipline (17.1%) during their military service. And it was observed that there were 71 crimes that 51 of the participants were associated with. The first drug used by the 12.5% (n=9) of the participants is synthetic cannabinoid. 24% (n=17) of them applied to the emergency department due to negative side effects they experienced due to SC use. 5.7% of respondents have little or no hope of stopping SD use. Conclusion: It was observed that the participants had problems in adaptation in education and military service processes; experienced intense legal problems, and had health problems due to substance effects. It is believed that both the improvement of preventive/therapeutic studies and the need to inform health and legal pesonelle about the users and effects of synthetic cannabinoids is substancial.